Lamut Sebagai Puisi Rakyat: Kajian Etnopedagogi: Lamut as Folk Poetry: An Ethnopedagogical Study - Fitriana, Arina; Mu’in, Fathul; Noortyani, Rusma; Ngalimun, Ngalimun (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Lamut is part of folk poetry among the Banjar people. The preservation of folk poetry is its transmission orally or by word of mouth. Lamut is also a tradition that must be preserved because its existence is almost extinct. This research aims to study the Lamut Koran as a form of teaching material that can be taught to students. Students are the right target to be invited to preserve Lamut because students are educated and must maintain traditions and culture. This research is a type of library research with a descriptive form of analysis. Library research is carried out by researchers by collecting data, recording, and processing the data so that results are found that are adapted to the theories used. The analysis technique used is content to identify data from a collection. The results of this research are that Lamut can be a mantra because it has mystical value, Lamut can be used as a poem because it tells a historical story, and Lamut can be used to convey a rhyme. This research also produces values found in lamut as folk poetry. These values include cultural values, social values, and religious values. This research also invites educators to use Lamut as teaching material for Indonesian language material at the SMP/MTs level. The use of Lamut as a form of folk poetry is a form of ethnopedagogical theory study. Ethnopedagogy is a learning model that emphasizes local wisdom values by using ethnicity as a teaching and learning process.